Preparation method of high-barrier composite film for packaging
By adding modified cellulose nano -crystals, antibacterials, and composite additives to polyvinyl resin, and the method of running into a membrane, the problem of insufficient blocking performance of the existing packaging film has significantly improved its barrier, antibacterial, antibacterial, and antibacterially. The flame retardant performance extended the shelf life.
Patent Information
- Application Number
- CN202411840914.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing packaging films have insufficient barrier properties when used, resulting in poor preservation performance for fresh physical objects.
By adding modified cellulose nano -crystals, antibacterials, and composite additives to polyvinyl alcohol resin, and undergoing a delayed film under specific temperature and speed conditions, high -resistance composite membranes are prepared.
It significantly enhances the stretching strength and toughness of the packaging film, improves its blocking performance, extends the shelf life of food and other items, and maintains stability in the humid environment, while improving flame retardant and antibacterial performance.
Smart Images

Figure CN119331288A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging film preparation, in particular to a method for preparing a high-barrier composite film for packaging. Background Art
[0002] Referring to the Chinese patent on a flame-retardant polyvinyl alcohol composite film and its application (Announcement No.: CN114507405A), the synthetic raw materials include by weight: 100-150 parts of PVA resin; 4-10 parts of polylactide; 0.2-35 parts of cellulose; 10-30 parts of plasticizer; 4-50 parts of flame retardant. A polyvinyl alcohol material with high-strength flame retardant properties and excellent mechanical properties and biodegradability is provided, which is used in the production of packaging bags for various products in life. However, when the packaging film is used, its barrier properties need to be improved, resulting in poor preservation performance for fresh objects; for this reason, the present invention proposes a method for preparing a high-barrier composite film for packaging to solve the above-mentioned problems. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high-barrier composite film for packaging, which solves the problems mentioned in the above background technology.
[0004] To achieve the above object, the present invention is implemented by the following technical scheme: A method for preparing a high barrier composite film for packaging, comprising the following preparation steps: Step 1: Mix 80-100 g of polyvinyl alcohol resin, 15-25 g of plasticizer and 8-10 g of modified cellulose nanocrystals; Step 2: Add 5-15g of antibacterial agent and 8-15g of composite auxiliary agent, stir at a speed of 100-200r / min for 25-40min, and cast into film at a temperature of 50°C to obtain a high barrier composite film for packaging.
[0005] Preferably, the preparation method of the modified cellulose nanocrystals is: (1) Pour 1.5-3 g of cellulose nanocrystals into 30-45 mL of anhydrous pyridine and ultrasonicate for 15-20 min; (2) Add 10-15 mL of acetic anhydride and 8-12 mL of catalyst in sequence, raise the temperature to 70-85°C, and start stirring the reaction for 6-8 hours; (3) After the reaction is completed, pour the product into 700-900 mL of distilled water and then place it at a temperature of 1-4°C for 45-60 minutes; (4) After centrifugation, wash with distilled water for 2-4 times, place in a dialysis bag for 2-4 days, take out, and adjust the pH value to neutral with a 10% mass fraction dilute hydrochloric acid solution; (5) The cellulose is placed in a vacuum freeze dryer for 3-4 days and then ground into powder to obtain modified cellulose nanocrystals.
[0006] Preferably, in (2), the catalyst is 4-dimethylaminopyridine.
[0007] Preferably, the preparation method of the composite auxiliary agent is: 1) Mix 3.2-5.5g lithium fluoride with 40-65mL hydrochloric acid solution and stir thoroughly until the reaction is complete; 2) Add 2-4.5g of titanium aluminum carbide in small amounts and multiple times under stirring; 3) After the addition is completed, heat to 40-50°C and react for 20-24 hours; 4) After centrifugation, the mixture is washed with deionized water until the pH value is 6, and then subjected to ultrasonic treatment. Finally, the mixture is placed in a vacuum freeze dryer for 50-80 minutes to obtain a composite auxiliary agent.
[0008] Preferably, in 1), the concentration of the hydrochloric acid solution is 7-9 mol / L.
[0009] Preferably, the preparation method of the antibacterial agent is: S1. pretreating chitosan; S2. Pour 3.5-8 g of tartaric acid into 40-45 g of deionized water, heat to 50-65°C and stir; S3, adding 0.6-0.9 g of pretreated chitosan, and continuing stirring for 15-25 min until it is completely dissolved; S4. Add 0.2-0.4 g of nanofiller and mix well to obtain the antibacterial agent.
[0010] Preferably, in S1, the specific method of pretreating chitosan is: pouring 1.5-4g of chitosan into 20-35mL of acetic acid solution, stirring until it is completely dissolved, filtering, adding NaOH solution to the filtrate, adjusting the pH of the solution to neutral, washing the precipitated chitosan and drying it.
[0011] Preferably, when washing chitosan, it is first washed with deionized water for 2-4 times, and then washed with isopropanol for 2-3 times; and then placed in a vacuum drying oven at 75-85° C. for drying.
[0012] Preferably, in S4, the nanofiller is selected from any one of nano-silicon dioxide and nano-titanium dioxide.
[0013] The present invention provides a method for preparing a high barrier composite film for packaging. Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the high-barrier composite film for packaging, since cellulose nanocrystals themselves have the characteristics of high strength and high modulus, after being modified and added to polyvinyl alcohol resin, the tensile strength and toughness of the packaging film can be significantly enhanced, making it more durable and not easy to break; the modified cellulose nanocrystals are combined with the polyvinyl alcohol resin to form a denser structure, effectively reducing the permeability of substances such as oxygen and water vapor, improving the barrier properties of the packaging film, extending the shelf life of food and other items, and at the same time reducing the water solubility of the packaging film and improving its stability in a humid environment.
[0014] (2) The preparation method of the high barrier composite film for packaging, lithium fluoride reacts with hydrochloric acid to generate lithium hydrogen fluoride and other substances, and the metal elements such as titanium and aluminum in titanium aluminum carbide form metal fluorides and the like in the reaction. These substances can cover the surface of the packaging film during combustion, isolate oxygen, and prevent further combustion, thereby improving the flame retardant properties of the packaging film; the addition of the composite auxiliary agent changes the thermal decomposition path of the polyvinyl alcohol resin, making it more difficult to decompose and produce combustible gases at high temperatures, reducing the fuel supply for combustion, and thereby enhancing the flame retardancy; at the same time, the composite flux can be filled into the molecular gaps of the polyvinyl alcohol resin, thereby improving the mechanical properties of the packaging film while reducing the permeation of gas molecules, thereby improving the barrier properties of the packaging film to oxygen, water vapor, etc., and helping to extend the shelf life of the packaged items.
[0015] (3) The preparation method of the high-barrier composite film for packaging comprises the following steps: adding an antimicrobial agent to fill the molecular gaps of the polyvinyl alcohol resin, thereby reducing the permeation of gas molecules and improving the barrier properties of the packaging film to oxygen, water vapor, etc.; the antimicrobial properties of the packaging film are improved by reacting chitosan with tartaric acid, etc. At the same time, the addition of nanofillers can inhibit the growth and reproduction of microorganisms, thereby further enhancing the antimicrobial function of the packaging film, which is beneficial to maintaining the sanitary quality of the packaged items. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 These are SEM images of the cross-sections of the composite membranes of Examples 1-3 and Comparative Examples 1-3 provided by the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the present technical solution, the plasticizer is propylene glycol. Example 1
[0019] A method for preparing a high barrier composite film for packaging, comprising the following preparation steps: Step 1: Mix 80 g of polyvinyl alcohol resin, 25 g of plasticizer and 10 g of modified cellulose nanocrystals; The preparation method of modified cellulose nanocrystals is as follows: pour 1.5 g of cellulose nanocrystals into 30 mL of anhydrous pyridine, and perform ultrasonic treatment for 15 min; add 10 mL of acetic anhydride and 8 mL of 4-dimethylaminopyridine in sequence, heat to 70°C, and start stirring reaction for 6 h; after the reaction is completed, pour the product into 700 mL of distilled water, and then place it at 1°C and let it stand for 45 min; after centrifugation, wash it twice with distilled water, put it into a dialysis bag for 2 days, take it out, and adjust the pH value to neutral with a dilute hydrochloric acid solution with a mass fraction of 10%; then put it into a vacuum freeze dryer for 3 days and grind it into powder to obtain modified cellulose nanocrystals; Step 2: add 15 g of antibacterial agent and 15 g of composite auxiliary agent, stir at a speed of 100 r / min for 25 min, and cast into film at a temperature of 50° C. to obtain a high barrier composite film for packaging; The preparation method of the antibacterial agent is as follows: pre-treating chitosan: pouring 1.5 g of chitosan into 20 mL of acetic acid solution, stirring until it is completely dissolved, filtering, adding NaOH solution to the filtrate, adjusting the pH of the solution to neutral, washing the precipitated chitosan twice with deionized water, and then washing it twice with isopropanol; finally, drying it in a vacuum drying oven at 75°C; pouring 3.5 g of tartaric acid into 40 g of deionized water, heating it to 50°C and stirring; adding 0.6 g of the pre-treated chitosan, and continuing to stir for 15 minutes until it is completely dissolved; adding 0.2 g of nano-silicon dioxide, mixing evenly, and obtaining the antibacterial agent; The preparation method of the composite auxiliary agent is as follows: 3.2 g of lithium fluoride is mixed with 40 mL of a hydrochloric acid solution with a concentration of 7 mol / L, and stirred until the reaction is complete; under stirring conditions, 25 g of titanium aluminum carbide is added in small amounts and multiple times; after the addition is completed, the temperature is raised to 40° C. and the reaction is performed for 20 hours; after centrifugation, the mixture is washed with deionized water until the pH value is 6, and then ultrasonic treatment is performed, and finally the mixture is placed in a vacuum freeze dryer for treatment for 50 minutes to obtain the composite auxiliary agent. Example 2
[0020] A method for preparing a high barrier composite film for packaging, comprising the following preparation steps: Step 1: Mix 90 g of polyvinyl alcohol resin, 20 g of plasticizer and 9 g of modified cellulose nanocrystals; The preparation method of the modified cellulose nanocrystals is as follows: pour 2 g of cellulose nanocrystals into 35 mL of anhydrous pyridine, and perform ultrasonic treatment for 18 minutes; add 12 mL of acetic anhydride and 10 mL of 4-dimethylaminopyridine in sequence, heat to 75°C, and start stirring reaction for 7 hours; after the reaction is completed, pour the product into 800 mL of distilled water, and then place it at a temperature of 2°C and let it stand for 50 minutes; after centrifugation, wash it with distilled water for 3 times, put it in a dialysis bag and take it out after 3 days, and adjust the pH value to neutral with a dilute hydrochloric acid solution with a mass fraction of 10%; then put it in a vacuum freeze dryer for 4 days and grind it into powder to obtain the modified cellulose nanocrystals; Step 2: add 10g of antibacterial agent and 12g of composite auxiliary agent, stir at a speed of 150r / min for 30min, and cast into film at a temperature of 50°C to obtain a high barrier composite film for packaging; The preparation method of the antibacterial agent is as follows: pre-treating chitosan: pouring 2.5 g of chitosan into 30 mL of acetic acid solution, stirring until it is completely dissolved, filtering, adding NaOH solution to the filtrate, adjusting the pH of the solution to neutral, washing the precipitated chitosan with deionized water for 3 times, and then washing it with isopropanol for 3 times; finally, drying it in a vacuum drying oven at 80°C; pouring 5 g of tartaric acid into 42 g of deionized water, heating it to 60°C and stirring it; adding 0.7 g of the pre-treated chitosan, and continuing to stir it for 20 minutes until it is completely dissolved; adding 0.3 g of nano titanium dioxide, mixing well, and obtaining the antibacterial agent; The preparation method of the composite auxiliary agent is as follows: 4.2 g of lithium fluoride is mixed with 55 mL of a hydrochloric acid solution with a concentration of 8 mol / L, and stirred until the reaction is complete; under stirring conditions, 3.2 g of titanium aluminum carbide is added in small amounts and multiple times; after the addition is completed, the temperature is raised to 45° C. and the reaction is performed for 22 hours; after centrifugation, the mixture is washed with deionized water until the pH value is 6, and then ultrasonic treatment is performed, and finally the mixture is placed in a vacuum freeze dryer for 65 minutes to obtain the composite auxiliary agent. Example 3
[0021] A method for preparing a high barrier composite film for packaging, comprising the following preparation steps: Step 1: Mix 100 g of polyvinyl alcohol resin, 15 g of plasticizer and 8 g of modified cellulose nanocrystals; The preparation method of the modified cellulose nanocrystals is as follows: 3 g of cellulose nanocrystals are poured into 45 mL of anhydrous pyridine, and ultrasonically treated for 20 minutes; 15 mL of acetic anhydride and 12 mL of 4-dimethylaminopyridine are added in sequence, the temperature is raised to 85°C, and the stirring reaction is started for 8 hours; after the reaction is completed, the product is poured into 900 mL of distilled water, and then placed at a temperature of 4°C for 60 minutes; after centrifugation, it is washed with distilled water for 4 times, and then placed in a dialysis bag for 4 days and then taken out, and the pH value is adjusted to neutral with a dilute hydrochloric acid solution with a mass fraction of 10%; and then placed in a vacuum freeze dryer for 4 days and ground into powder to obtain the modified cellulose nanocrystals; Step 2: Add 5 g of antibacterial agent and 8 g of composite auxiliary agent, stir at a speed of 200 r / min for 40 min, and cast into a film at a temperature of 50° C. to obtain a high barrier composite film for packaging; The preparation method of the antibacterial agent is as follows: pre-treating chitosan: pouring 4 g of chitosan into 35 mL of acetic acid solution, stirring until it is completely dissolved, filtering, adding NaOH solution to the filtrate, adjusting the pH of the solution to neutral, washing the precipitated chitosan with deionized water for 4 times, and then washing it with isopropanol for 3 times; finally, drying it in a vacuum drying oven at 85°C; pouring 8 g of tartaric acid into 45 g of deionized water, heating it to 65°C and stirring it; adding 0.9 g of the pre-treated chitosan, and continuing to stir it for 25 minutes until it is completely dissolved; adding 0.4 g of nano titanium dioxide, mixing well, and obtaining the antibacterial agent; The preparation method of the composite auxiliary agent is as follows: 5.5 g of lithium fluoride is mixed with 65 mL of a hydrochloric acid solution with a concentration of 9 mol / L, and stirred until the reaction is complete; under stirring conditions, 4.5 g of titanium aluminum carbide is added in small amounts and multiple times; after the addition is completed, the temperature is raised to 50° C. and the reaction is performed for 24 hours; after centrifugation, the mixture is washed with deionized water until the pH value is 6, and then ultrasonically treated, and finally placed in a vacuum freeze dryer for treatment for 80 minutes to obtain the composite auxiliary agent.
[0022] Comparative Example 1 Compared with Example 1, the difference is that the modified cellulose nanocrystals in Example 1 are replaced by cellulose nanocrystals; the rest remains unchanged.
[0023] Comparative Example 2 Compared with Example 1, the difference is that the composite auxiliary agent in Example 1 is not added; the rest remains unchanged.
[0024] Comparative Example 3 Compared with Example 1, the difference is that the antibacterial agent in Example 1 is replaced by chitosan; the rest remains unchanged.
[0025] Oxygen barrier test: Tested according to GB / T10004-2008 standard; the results are shown in Table 1; the calculation formula of oxygen permeability coefficient is: ; In the formula, is the oxygen permeability coefficient, cm 3 m / (m 2 ·d·Pa); is the oxygen transmission rate, cm 3 / (cm 2 ·d); D is the film thickness, m; is the oxygen pressure difference on both sides of the membrane, Pa.
[0026] Water vapor barrier test: The test was conducted according to the standard of GB / T26253-2010, with a relative humidity of 50% and a test temperature of 25°C. The moisture permeability test was conducted after preheating for 1 hour. The water vapor permeability was directly output by the instrument, and the water vapor permeability coefficient was calculated (the results are shown in Table 1): ; In the formula, is the water vapor transmission coefficient, g·m / (m 2 ·d·Pa); is the water vapor transmission rate, g / (m 2 ·d); D is the film thickness, m; is the oxygen pressure difference on both sides of the membrane, Pa; is the saturated vapor pressure of water at the measured temperature, Pa; is the relative humidity of the upper part of the test chamber, %; is the relative humidity in the lower part of the test chamber, %.
[0027] Table 1
[0028] Antibacterial rate test: The test was conducted according to the standard of GB / T21510-2008; the results are shown in Table 2.
[0029] Tensile strength test: The test was conducted according to the standard of GB / T1040.1-2006; the results are shown in Table 2.
[0030] Flame retardant performance test: tested according to the standard of QB / T5786-2022; the results are shown in Table 2.
[0031] Vertical burning rating (UL-94) test: tested according to GB / T5455-2014 standard; the results are shown in Table 2.
[0032] Table 2
[0033] Figure 1 In the embodiment, each letter is: A-Example 1, B-Example 2, C-Example 3, D-Comparative Example 1, E-Comparative Example 2, F-Comparative Example 3; Figure 1 As shown in the figure, the surface of the CD packaging composite film is relatively rough and has fractures, while the surface of the AC packaging composite film is smooth and flat without any gaps, and has a tight molecular structure without fractures.
[0034] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0035] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high barrier composite film for packaging, characterized in that: The method comprises the following preparation steps: Step 1: Mix 80-100 g of polyvinyl alcohol resin, 15-25 g of plasticizer and 8-10 g of modified cellulose nanocrystals; Step 2: Add 5-15g of antibacterial agent and 8-15g of composite auxiliary agent, stir at a speed of 100-200r / min for 25-40min, and cast into film at a temperature of 50°C to obtain a high barrier composite film for packaging.
2. The method for preparing a high barrier composite film for packaging according to claim 1, characterized in that: The preparation method of the modified cellulose nanocrystals is: (1) Pour 1.5-3 g of cellulose nanocrystals into 30-45 mL of anhydrous pyridine and ultrasonicate for 15-20 min; (2) Add 10-15 mL of acetic anhydride and 8-12 mL of catalyst in sequence, raise the temperature to 70-85°C, and start stirring the reaction for 6-8 hours; (3) After the reaction is completed, pour the product into 700-900 mL of distilled water and then place it at a temperature of 1-4°C for 45-60 minutes; (4) After centrifugation, wash with distilled water for 2-4 times, place in a dialysis bag for 2-4 days, take out, and adjust the pH value to neutral with a 10% mass fraction dilute hydrochloric acid solution; (5) The cellulose is placed in a vacuum freeze dryer for 3-4 days and then ground into powder to obtain modified cellulose nanocrystals.
3. The method for preparing a high barrier composite film for packaging according to claim 2, characterized in that: In the above (2), the catalyst is 4-dimethylaminopyridine.
4. The method for preparing a high barrier composite film for packaging according to claim 1, characterized in that: The preparation method of the composite auxiliary agent is: 1) Mix 3.2-5.5g lithium fluoride with 40-65mL hydrochloric acid solution and stir until the reaction is complete; 2) Add 2-4.5g of titanium aluminum carbide in small amounts and multiple times under stirring; 3) After the addition is completed, heat to 40-50°C and react for 20-24 hours; 4) After centrifugation, the mixture is washed with deionized water until the pH value is 6, and then subjected to ultrasonic treatment. Finally, the mixture is placed in a vacuum freeze dryer for 50-80 minutes to obtain a composite auxiliary agent.
5. The method for preparing a high barrier composite film for packaging according to claim 4, characterized in that: In the above 1), the concentration of the hydrochloric acid solution is 7-9 mol / L.
6. The method for preparing a high barrier composite film for packaging according to claim 1, characterized in that: The preparation method of the antibacterial agent is: S1. pretreating chitosan; S2. Pour 3.5-8 g of tartaric acid into 40-45 g of deionized water, heat to 50-65°C and stir; S3, adding 0.6-0.9 g of pretreated chitosan, and continuing stirring for 15-25 min until it is completely dissolved; S4. Add 0.2-0.4 g of nanofiller and mix well to obtain the antibacterial agent.
7. The method for preparing a high barrier composite film for packaging according to claim 6, characterized in that: In S1, the specific method of chitosan pretreatment is: pour 1.5-4g chitosan into 20-35mL acetic acid solution, stir until it is completely dissolved, filter, add NaOH solution to the filtrate, adjust the pH of the solution to neutral, wash the precipitated chitosan and then dry it.
8. The method for preparing a high barrier composite film for packaging according to claim 7, characterized in that: When washing chitosan, first use deionized water to wash 2-4 times, then use isopropanol to wash 2-3 times; and place in a vacuum drying oven at 75-85°C for drying.
9. The method for preparing a high barrier composite film for packaging according to claim 6, characterized in that: In the above S4, the nano filler is selected from any one of nano silicon dioxide and nano titanium dioxide.
Citation Information
Patent Citations
Flame-retardant polyvinyl alcohol composite film and application thereof
CN114507405A
Acetylated cellulose nanocrystalline composite modified biomass-based polyester material and preparation method thereof
CN105754308A
Preparation of a nanometer cellulose / chitosan / polyvinyl alcohol composite membrane through a tape casting method, and applications of the composite membrane in biological antibacterial membranes
CN106867042A
High-strength flame-retardant MXene / phosphorylated cellulose filament composite film and preparation method thereof
CN115322443A
Antibacterial film and preparation method thereof
CN115785597A
Cited By
Co-extrusion composite barrier packaging film and preparation process thereof
CN120056547A